2008
DOI: 10.1152/ajpheart.00379.2008
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial ischemic postconditioning against ischemia-reperfusion is impaired in ob/ob mice

Abstract: Ischemic postconditioning (IPCD) significantly reduces infarct size in healthy animals and protects the human heart. Because obesity is a major risk factor of cardiovascular diseases, the effects of IPCD were investigated in 8- to 10-wk-old leptin-deficient obese (ob/ob) mice and compared with wild-type C57BL/6J (WT) mice. All animals underwent 30 min of coronary artery occlusion followed by 24 h of reperfusion associated or not with IPCD (6 cycles of 10-s occlusion, 10-s reperfusion). Additional mice were kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
7
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 44 publications
11
105
7
2
Order By: Relevance
“…In parallel, the variations of phosphatase levels mirrored those of corresponding kinase phosphorylations as PTEN and MKP-3 were concomitantly decreased by regular exercise. This point is of major importance as it is known that phosphatases limit the efficacy of some cardioprotective strategies such as pre-or postconditioning during aging or obesity [9,29,30]. One could suggest that reduced phosphatases expression would be responsible for the activation of survival kinases which is known to be a crucial event for protecting the myocardium against myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In parallel, the variations of phosphatase levels mirrored those of corresponding kinase phosphorylations as PTEN and MKP-3 were concomitantly decreased by regular exercise. This point is of major importance as it is known that phosphatases limit the efficacy of some cardioprotective strategies such as pre-or postconditioning during aging or obesity [9,29,30]. One could suggest that reduced phosphatases expression would be responsible for the activation of survival kinases which is known to be a crucial event for protecting the myocardium against myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it has been previously reported that both pre-and postconditioning failed to reduce infarct size in obese animals probably because of their inability to activate the cardioprotective signalling pathways through kinase phosphorylations. [7][8][9]. Nevertheless, it is known that exercise is able to decrease cardiac events and mortality in obese or overweight patients [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have confirmed the role for Akt and Erk1/2 in the setting of IPost in both non-diseased animal hearts and diseased ones [215,216] as well as human atrial muscle [217]. Interestingly, obese mice have been reported to be resistant to IPost protection, and this finding was associated with insufficient activation of the RISK pathway in the hearts harvested from obese animals compared to control ones [218]. This finding underscores the importance of using relevant experimental animal models capable of simulating disease pathologies present in patients with coronary heart disease.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 87%
“…Wagner and co-workers [236] have shown loss of preconditioning in a rat model of established metabolic syndrome. In the leptin-deficient (ob/ob) mouse cardiac benefit from postconditioning is impaired [237], while there is also evidence of failed preconditioning in obese insulin-resistant rats [238]. Failure of a variety of cardioprotective interventions involving multiple and varied triggers, implicates dysfunction of the signalling paths of the RISK pathway that are common to these interventions.…”
Section: The Effect Of Insulin Resistance On Myocardial Pro-survival mentioning
confidence: 99%